"Marielle, presente": Metaleptic temporality and the enregisterment of hope in Rio de Janeiro. (7th December 2020) - Silva, Daniel N.; Lee, Jerry Won
Abstract: This article looks to the assassination of Marielle Franco, a queer Black councilwoman from the Complexo da Maré favela in Rio de Janeiro, to outline a principled metacomunicative action toward "hope." Empirically, it unpacks features of the pragmatics of her discourse, along with that of mourners who knew her. We identify two main features in their discourse that point to the enregisterment of hope, i.e. to ways in which their communicative practices have been attuned to avoid despair by propelling an alternative indexing of time, authority, and forms of life. These features are as follows: metaleptic temporality, i.e. the reinsertion of Marielle's agentive time into the temporal universe of heroes; and papo reto, a translational and performative practice of scaling bureaucratic and economic talk into local registers. Finally, we point to the habituated and pedagogic dimension of this sociolinguistics of hope, in part responsible for the fractalization and performativity of the mourning movement. Resumo: Este artigo estuda o assassinato de Marielle Franco, uma vereadora negra e lésbica do Complexo da Maré no Rio de Janeiro, de forma a delinear os princípios de uma ação metacomunicativa direcionada à "esperança". Empiricamente, analisam‐se características do discurso de Marielle e do movimento de luto que se formou depois de sua morte trágica. Identificamos duas características básicas no discurso desses agentes que apontam para o enregistramento da esperança, i.e. para modos em que suas práticas comunicativas têm sido moldadas de forma a evitar o desespero por meio da projeção de índices alternativos de tempo, autoridade e formas de vida. Essas características são: temporalidade metaléptica, i.e. a reinserção do tempo agentivo de Marielle no universo temporal dos heróis; e papo reto, uma prática tradutória e performativa que "escala" a fala burocrática e econômica em registros locais. Finalmente, apontamos para a dimensão habituada e pedagógica dessa sociolinguística da esperança, em parte responsável pela fractalização e performatividade do movimento de luto.